On saturation control of a non-ideal vibrating portal frame foundation type shear-building - Felix, JLP; Balthazar, José Manoel [UNESP]; Brasil, RMLRF (Sage Publications Ltd, 2005)
In this paper, we examine the nonlinear control method based on the saturation phenomenon and of systems coupled with quadratic nonlinear ties applied to a shear-building portal plane frame foundation that supports an unbalanced direct cut-rent with limited power supply (non-ideal system). We analyze the equations of motion by using the method of averaging and numerical simulation. The interaction of the non-ideal structure with the saturation controller may lead to the occurrence of interesting phenomena during the forward passage through the several resonance states of the systems. Special attention is focused on passage through resonance when the non-ideal excitation frequency is near the portal frame natural frequency and when the non-ideal system frequency is approximately twice the controller frequency (two-to-one internal resonance).
Keywords: saturation control; non-ideal system; portal frame structure